An Overview on Nalbuphine - Ali Khalil, Samar Hamdy; Sayed Ahmed, Ashraf Said; Ahmed, Farahat Ibrahim; Mohammed Hussein, Ahmed Beniamen (Journal of Neonatal Surgery, 2025)
Nalbuphine is a synthetic opioid analgesic with mixed agonist–antagonist activity, acting as a κ-opioid receptor agonist and a μ-opioid receptor antagonist. It has been widely used for the management of moderate to severe pain and as an adjunct in anesthesia. Compared with traditional opioids such as morphine, nalbuphine provides effective analgesia with a lower risk of respiratory depression, pruritus, and dependence, making it a valuable option in perioperative and postoperative settings